Playing for the planet: designing toys that foster sustainable values - Barreto, Mary L.; Scott, Michelle; Oakley, Ian; Karapanos, Evangelos; Nunes, Nuno J.; Gomes, Sofia; Gomes, Joana (My University, 2013)
The children of today are the adults of tomorrow, for this reason it is essential to educate this generation about sustainable values, such as recycling and reducing waste and energy consumption. By targeting children's main activity of playing and toys, the design of a toy that instills sustainable values is illustrated through PlayGreen, a prototype of an interactive application. We argue that this type of toy should be designed according to children's cognitive development and their learning skills, as well as conforming to a value centered design process. This paper focuses on Piaget's cognitive development theory, more specifically, the concrete operational stage processes, which occur between the ages of seven and eleven years old. Our prototype is an application focusing on the value of resource management and allows children to create new toys from household materials. This prototype was tested with 8 and 9 year old children via a Wizard of Oz method. The prototype successfully integrated a value related to sustainability and the users were able to manipulate it easily as it was adequate to their cognitive skills.
Keywords: Children; Design guidelines; Learning; Play; Sustainability; User characteristics; Value development